Euphorbia-Derived Natural Products with Potential for Use in Health Maintenance - Salehi, Bahare; Iriti, Marcello; Vitalini, Sara; Antolak, Hubert; Pawlikowska, Ewelina; Kręgiel, Dorota; Sharifi-Rad, Javad; Oyeleye, Sunday I.; Ademiluyi, Adedayo O.; Czopek, Katarzyna; Staniak, Mariola; Custódio, Luísa; et al. (Biomolecules (Basel, Switzerland), 2019)
Euphorbia genus (Euphorbiaceae family), which is the third largest genus of angiosperm plants comprising ca. 2000 recognized species, is used all over the world in traditional medicine, especially in the traditional Chinese medicine. Members of this taxa are promptly recognizable by their specialized inflorescences and latex. In this review, an overview of Euphorbia-derived natural products such as essential oils, extracts, and pure compounds, active in a broad range of biological activities, and with potential usages in health maintenance, is described. The chemical composition of essential oils from Euphorbia species revealed the presence of more than 80 phytochemicals, mainly oxygenated sesquiterpenes and sesquiterpenes hydrocarbons, while Euphorbia extracts contain secondary metabolites such as sesquiterpenes, diterpenes, sterols, flavonoids, and other polyphenols. The extracts and secondary metabolites from Euphorbia plants may act as active principles of medicines for the treatment of many human ailments, mainly inflammation, cancer, and microbial infections. Besides, Euphorbia-derived products have great potential as a source of bioactive extracts and pure compounds, which can be used to promote longevity with more health.